Airway management in cervical spine ankylosing spondylitis: Between a rock and a hard place - Naveen Eipe; Susan Fossey; Stephen P Kingwell (Indian Journal of Anaesthesia, 2013)
We report the perioperative course of a patient with long standing ankylosing spondylitis with severe dysphagia due to large anterior cervical syndesmophytes at the level of the epiglottis. He was scheduled to undergo anterior cervical decompression and the surgical approach possibly precluded an elective pre-operative tracheostomy. We performed a modified awake fibreoptic nasal intubation through a split nasopharyngeal airway while adequate oxygenation was ensured through a modified nasal trumpet inserted in the other nares. We discuss the role of nasal intubations and the use of both the modified nasopharyngeal airways we used to facilitate tracheal intubation. This modified nasal fibreoptic intubation technique could find the application in other patients with cervical spine abnormalities and in other anticipated difficult airways.